Penerapan Pembelajaran Kooperatif Learning Model Snowball Throwing untuk Meningkatkan Hasil Belajar Sejarah pada Siswa SMA - Lusia Rini Idriastuti (Jurnal Syntax Transformation, 2021)
This study aims to improve learning outcomes by using the Snowball Throwing model of History learning in class XII IPS 2 students at SMA Negeri 3 Magelang in the 2019/2020 academic year. This research is a Classroom Action Research (CAR). The essence of classroom action research to solve problems that occur in the classroom is the result of learning history under the KKM. This study uses 2 cycles which include planning, implementation, observation, and reflection activities. In this study, the data sources came from observations, document texts, questionnaires, photos, and learning outcomes tests. The validity of the data in this study uses triangulation, which consists of triangulation of data sources and methods, while the data analysis uses quantitative and descriptive quantitative analysis. The results of this study indicate that the application of the Snowball Throwing method which was developed with discussion models, oral question and answer can improve student learning outcomes. Completeness of student learning outcomes in pre-cycle is 34.48%, cycle I is 65.52%, cycle II is 82 ,75%. Student learning outcomes in the first cycle increased 31.03% from the pre-cycle. And in the second cycle increased 17.24% from the first cycle. The Snowball Throwing learning model was proven to be able to improve student learning outcomes